2015
DOI: 10.1128/jcm.02926-14
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Microbiological Characteristics of Eggerthella lenta Bacteremia

Abstract: e Eggerthella lenta is an emerging pathogen that has been underrecognized due to historical difficulties with phenotypic identification. Until now, its pathogenicity, antimicrobial susceptibility profile, and optimal treatment have been poorly characterized. In this article, we report the largest cohort of patients with E. lenta bacteremia to date and describe in detail their clinical features, microbiologic characteristics, treatment, and outcomes. We identified 33 patients; the median age was 68 years, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
84
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(90 citation statements)
references
References 60 publications
2
84
1
Order By: Relevance
“…Recent reports have shown that several E. lenta infections were associated with the use of intrauterine devices, spondylodiscitis, female genital tract infections, cutaneous abscesses, and bacteremia (in Crohn's disease patients) [1][2][3][4]12]. These data emphasize the importance of further investigation for bacterial virulence factors.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Recent reports have shown that several E. lenta infections were associated with the use of intrauterine devices, spondylodiscitis, female genital tract infections, cutaneous abscesses, and bacteremia (in Crohn's disease patients) [1][2][3][4]12]. These data emphasize the importance of further investigation for bacterial virulence factors.…”
Section: Discussionmentioning
confidence: 90%
“…Eggerthella lenta is part of the normal human intestinal flora and has been most commonly associated with infections arising from the gastrointestinal tract [1]. Predisposing conditions include gastrointestinal tract disease, malignancies, hepatobiliary disease, immobilization, bedsores, diabetes mellitus, and stroke [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…We kept using meropenem as an empiric therapy after the laparoscopic drainage and debridement of the rectovesical pouch abscess because the causative bacterium was unknown. After 1 week , E. lenta , which is susceptible to antibiotics with much smaller spectra than meropenem,11 was isolated from the cultures of the pus collected from the rectovesical pouch abscess. However, we kept administering meropenem because we did not know whether the splenic abscesses had been caused by E. lenta alone.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, research has recently confirmed a clear relationship between Actinomyces and conventional adenoma (66), one of the two main precursors of colorectal cancer. Finally, Eggerthella is an opportunistic pathogen often associated with serious gastrointestinal pathology (67). One might question the role of these taxa as key players in the phase transition of the microbiota and wonder whether they are more susceptible to perturbations than the most abundant taxa.…”
Section: Discussionmentioning
confidence: 99%